Expression of insulin-like growth factor binding protein-2 (IGFBP-2) gene in negative and positive human cytomegalovirus glioblastoma multiforme tissues - Ahani, Narges; Karimi Arzenani, Mohsen; Shirkoohi, Reza; Rokouei, Mohammad; Alipour Eskandani, Majid; Nikravesh, Abbas (Medical oncology (Northwood, London, England), 2014)
Glioblastoma multiforme (GBM), a WHO grade IV malignant glioma, is the most common and lethal primary brain tumor in adults and has but few treatments. The median survival of glioblastoma patients is 12 months. The (possible) relationship between human cytomegalovirus (HCMV) infection and cancer has been investigated for decades. Detection of viral DNA, mRNA and/or antigens in tumor tissues suggests that HCMV infection has a role to play in the etiology of several human malignancies. HCMV gene products can promote the various signaling pathways critical to tumor growth, including platelet derived growth factor receptor, phosphatidyl inositol 3-kinases (PI3K/AKT), signal transducer and activator of transcription 3 and glycogen synthase kinase 3 beta that are involved in apoptosis, angiogenesis, invasion and immune evasion. Insulin-like growth factor binding protein 2 (IGFBP2) is a biomarker of the PI3K/AKT pathway so we decided to evaluate the expression of this gene in 3 groups: HCMV-negative GBM tissues, HCMV-positive GBM tissues and non-tumor tissues. The presence of HCMV was assessed according to our previous article. HCMV was present in %75 of glioblastoma tissues. Then RNA was extracted, cDNA was synthesized, and real-time PCR was performed. Then, the rate of increased expression was calculated using the Livac or 2 −ΔΔCt . ΔCt of samples in the three groups were compared using analysis of variance (ANOVA). The expression of IGFBP2 gene relative to GAPDH gene in HCMV-negative glioblastoma tissues and HCMV-positive glioblastoma tissues, respectively, was increased 5.486 and 15.032 times compared to non-neoplastic brain tissues. ANOVA tests showed that the difference of mean ΔCt for IGFBP2 gene between healthy subjects and patients with HCMV-positive and HCMV-negative glioblastoma tumors statistically significant.